Tinjauan Penerapan E-Puskesmas Pada Puskesmas Babelan I Kabupaten Bekasi - Magdalena, Selvy; Yulia, Noor; Sonia, Dina; Fannya, Puteri (Indonesian of Health Information Management Journal (INOHIM), 2023)
AbstractHealth Centers take advantage of advances in information technology to meet the demands for fast and accurate health services. The ePuskesmas application manifests technology and communication, significantly enhancing excellent patient service. The objective is to review the implementation of ePuskesmas at the Babelan I Health Center in Bekasi Regency. Descriptive Research Methods with a qualitative approach to analysis. Data collection techniques through observation and interviews with six research informants using interview guide instruments. Research Results: The contents of the SPO of ePuskesmas administration do not follow the ePuskesmas ManualBook. At the Puskesmas, units still have not implemented ePuskesmas (Medical Record Unit, HIV Poly, Leprosy Poly, Pharmacy Unit). In practice, not all officers can use ePuskesmas optimally. The main obstacle factor is that the Man (Human Resources) is still lacking in terms of quality and quantity, the ePuskesmas filling method is not under the Manual Book, the data input material to ePuskesmas is not complete, sometimes the system is not integrated, Machine The availability of facilities and infrastructure is still lacking. The conclusion is that implementing ePuskesmas in the Babelan I Health Center Outpatient Unit is not optimal because not all units use ePuskesmas according to the Manual Book. Suggestion: The SOP for the procedures for implementing ePuskesmas is revised and disseminated to all units.Keywords: ePuskesmas, SPO, Constraint factor AbstrakPuskesmas memanfaatkan kemajuan informasi teknologi dalam memenuhi tuntutan pelayanan kesehatan yang cepat dan akurat. Aplikasi ePuskesmas merupakan wujud penerapan teknologi dan komunikasi yang memberikan kontribusi besar dalam meningkatkan pelayanan prima kepada pasien. Tujuan Penelitian: meninjau Penerapan ePuskesmas pada Puskesmas Babelan I Kabupaten Bekasi. Metode Penelitian Deskriptif dengan analisa pendekatan secara kualitatif. Teknik pengumpulan data melalui observasi dan wawancara kepada 6 orang informan penelitian dengan menggunakan instrumen pedoman wawancara. Hasil Penelitian: Isi dari SPO tata laksana ePuskesmas belum sesuai dengan ManualBook ePuskesmas, di Puskesmas masih ada unit yang belum menerapkan ePuskesmas (Unit Rekam Medis, Poli HIV, Poli Kusta, Unit Farmasi), dalam pelaksanaannya belum semua petugas dapat menggunakan ePuskesmas secara optimal, Faktor kendala utama adalah Man (Sumber Daya Manusia) masih kurang dari segi kualitas dan kuantitas, Method (Metode) pengisian ePuskesmas belum sesuai ManualBook, Material (Bahan) data yang di input ke ePuskesmas belum lengkap, kadang sistem tidak terintegrasi, Machine (Mesin) Ketersediaan sarana dan prasarana masih kurang. Kesimpulan: Penerapan ePuskesmas di Unit Rawat Jalan Puskesmas Babelan I belum optimal karena belum semua Unit menggunakan ePuskesmas sesuai dengan ManualBook. Saran: SPO tata cara penerapan ePuskesmas direvisi dan disosialisasikan untuk semua unit.Kata Kunci: ePuskesmas, SPO, Faktor kendala